PENGARUH MEDIA POSTER TERHADAP HASIL BELAJAR PEMBELAJARAN IPA SISWA KELAS V - Elda Ferayani; Noviati; Robert Budi Laksana (STKIP Subang, 2023)
Natural Science is a learning component that is very close to human activities in everyday life. Therefore, the difficulties experienced in learning science are difficulties in understanding the material presented due to the lack of use of media in the learning process and has an impact on low student learning outcomes. Based on this, the problem in this study is the low learning outcomes of fifth grade students in science learning.The purpose of this study was to determine the effect of media posters on learning outcomes in science learning for fifth grade students. The method used was a quantitative method with an experimental type. The design used is Quasi Experimental with the form of Nonequivalent Control Group Design. The population in this study were fifth grade students at SD Negeri 22 Palembang. The sample in this study were students of class VA as the control class and class VB as the experimental class. Data collection techniques in this research are Tests and Documentation. The pretest results for the experimental class with an average of 54.1 and for the control class with an average of 54.8 for the posttest results in the experimental class have an average value of 82.3 and for the control class have an average value of 65.6. Based on the calculation of the normality test, the data obtained by the experimental group was -0.04 and the control group was 0.20. Homogeneity test results for fcount ≤ ftable or 0.62 ≤ 2.40, it can be said to be homogeneous. Testing the hypothesis from the results of the calculation of the t test obtained the value obtained tcount> ttable or 19.19> 2.048 with db 28 at a significant level of 5%. So it can be concluded that the hypothesis states that there is an effect of poster media on the learning outcomes of fifth grade students in science learning. Keywords: Poster Media, Learning Outcomes, Science Learning